Mitigation of water limitation effects on flower traits, fruit development and yield of chili pepper (Capsicum annuum L.) by brassinosteroid mimic - Sonjaroon, Weerasin; Jutamaneea, Kanapol; Suksamrarn, Apichart; Khamsuk, Ornusa (Agriculture and Natural Resources, 2025)
Importance of the work: 7,8-Dihydro-8α-20-hydroxyecdysone (DHECD) is a brassinosteroid mimic, that could enhance the resilience and sustainability of chili pepper cultivation, which frequently has water shortage problems, particularly in Northeast Thailand. Objectives: to investigate the impact of DHECD on chili pepper traits, flower anatomy, fruit development and yield under well-irrigated and water-limited conditions. Materials & Methods: Four treatments (well irrigated with and without DHECD and water limitation with and without DHECD) were applied during the floral induction stage of development. Under water-limited conditions (50% pot water capacity for 5 d), 0.1 μM DHECD was applied to plants aged 60 d during the floral induction stage of reproductive development. Results: DHECD enhanced floral length, influencing flower anatomy by promoting the tissue layer that merged with the ovary wall to form the pericarp, as well as facilitating tapetum layer formation under water-limited conditions. DHECD alleviated the delays in flower, microspore and fruit development caused by the water limitation. Furthermore, DHECD ensured regular fruit growth, thick pericarp layer development, increased pollen germination, a high fruit set percentage and reduced fruit drop percentage. Main finding: DHECD application during the floral induction stage strategically enhanced chili pepper resilience to water limitation, presenting a valuable approach for sustainable production in water-limited environments.